2014
DOI: 10.1016/j.bjorl.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Electrocochleography for Ménière's disease: is it reliable?

Abstract: Electrocochleography is a valuable tool in the diagnosis of hydrops, as it is a non-invasive, easy to handle procedure, which offers new techniques to increase the sensitivity of the test, and thereby assists otolaryngologists in the management of Ménière's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…ECoG may not correlate with the stage of disease, duration of symptoms, patient history, and audiometric findings all the time (6,(36)(37)(38). Moreover, even if vertigo attacks disappear completely after treatment, the SP/AP ratio does not recover (38).…”
Section: Ecogmentioning
confidence: 99%
See 1 more Smart Citation
“…ECoG may not correlate with the stage of disease, duration of symptoms, patient history, and audiometric findings all the time (6,(36)(37)(38). Moreover, even if vertigo attacks disappear completely after treatment, the SP/AP ratio does not recover (38).…”
Section: Ecogmentioning
confidence: 99%
“…Moreover, even if vertigo attacks disappear completely after treatment, the SP/AP ratio does not recover (38). Besides that, ECoG is an informative test, in prediction of when the disease will be bilateral, decision of treatment choices, or renewal of the treatment method (6,36,37). The sensitivity of the ECoG test in the diagnosis of MD variants, vestibular MD (recurrent vestibulopathy) and cochlear MD (acute low tone sensorineural hearing loss), were reported to be 62.5% and 67%, respectively (39).…”
Section: Ecogmentioning
confidence: 99%
“…Lamounier et al also found in the systematic review that the analysis of the SP/AP ratio curve of the transtympanic electrocochleography did not necessarily increase sensitivity in the diagnosis of hydrops when compared with the SP/AP amplitude [14,[16][17][18].…”
Section: Electrocochleography (Ecochg)mentioning
confidence: 96%
“…In most studies selected, the transtympanic electrode is the most widely used. EcochG in MD presents a variable sensitivity, as in cases of hearing loss due to disease progression, patients may experience a reduction in the amplitude of AP due to loss of auditory nerve fibers [14][15][16][17].…”
Section: Electrocochleography (Ecochg)mentioning
confidence: 99%
“…Although more relective of real life than an artiicial experiment, retrospective observational studies are susceptible to bias [4].…”
mentioning
confidence: 99%